Preservation Efforts of Riau Malay Dance through Persembahan Dance Game - Syefriani Syefriani; Panji Rachmat Setiawan; Elleanor Virgiana (Universitas Negeri Medan, 2025)
Persembahan Dance is a traditional Malay dance of Riau, possessing high cultural significance as a dance to welcome honored guests and is an integral component of Riau Malay cultural heritage. However, with the progression of time and globalization, there is a risk if the preservation of Persembahan Dance is not undertaken. This research aims to analyze the preservation efforts of Persembahan Dance through the development of an engaging game application for young generations. The research methodology employed is descriptive analysis with a qualitative approach, encompassing observation, interviews, and documentation. This study also identifies the preservation efforts made by the government, educational institutions, artists, and art studios. The government supports preservation by patenting Persembahan Dance as part of the regional cultural heritage and incorporating it into official events. Educational institutions integrate Persembahan Dance into the Cultural Arts curriculum and extracurricular activities for young generations. Artists and art studios contribute through education and cultural promotion both nationally and internationally. Conversely, the development of Persembahan Dance through educational games using the Game Development Life Cycle (GDLC) method creates an innovation that can attract young people's interest in learning and appreciating traditional dance while preserving cultural values. This study is expected to provide a significant contribution to the preservation of Riau Malay art and promote public awareness of the importance of maintaining cultural heritage.